Funding of Public Universities Panacea for Effective Implementation of Core Curriculum and Minimum Academic Standards (CCMAS) in Nigeria - F, Ohiare-Udebu M.; Ogunode, Niyi Jacob; Sarafadeen, RAUF Olaiya; AYOKO, Victor Olugbenga (International Journal on Integrated Education, 2023)
Recently, the National Universities Commission released the Core Curriculum and Minimum Academic Standards (CCMAS) for official implementation in Nigerian universities. Implementation of the curriculum such as the Core Curriculum and Minimum Academic Standards (CCMAS) required both availabilities of human and materials resources in the right quantities and qualities. Adequate funding is key for an effective curriculum implementation. This paper discussed the importance of adequate funding of the Nigerian university system as a panacea for the effective implementation of the Core Curriculum and Minimum Academic Standards (CCMAS) in the universities. Secondary data were employed. The data were collected from print and online publications. This paper posits that adequate funding of the Nigerian university system will lead to the effective implementation of the Core Curriculum and Minimum Academic Standards (CCMAS) in Nigerian universities. Adequate funding will also guarantee the provision of adequate staff (academic and non-academic staff), infrastructure facilities, instructional materials, capacity-building programmes and curriculum monitoring and evaluation. It is suggested that the federal and state governments should adequately fund the universities for effective implementation of the Core Curriculum and Minimum Academic Standards (CCMAS) curriculum in universities across the country.